Current Status and Challenges of Two Overlooked Medicinal Plants Cestrum diurnum and Cestrum nocturnum: A Review - Fakhrah, Shafquat; Mohanty, Chandra Sekhar; Kumari, Alka (Pharmacognosy Reviews)
Previously, most pharmaceutical compounds were produced from naturally occurring components in plants. However, many plant species with high therapeutic potential have been overlooked or neglected. In an era of unfavorable climatic and human changes that endanger natural vegetation worldwide, it is critical to find and research these neglected medicinal plants. The genus Cestrum belonging to the family Solanaceae, which includes Cestrum diurnum and Cestrum nocturnum, contains a wide variety of important nutritional, chemical and medicinal properties. Both plants have become popular garden plants, but they also possess therapeutic potential. C. diurnum has been shown to possess antioxidant, hepatoprotective, larvicidal and cardioactive properties, also has potential to make a supplement of vitamin D3, while C. nocturnum has anti-inflammatory, analgesic, antimicrobial and anticancer effects. The distribution, physical traits, ecological preferences and ethnobotanical uses of both plant species are explored in the present review, which demonstrates that C. nocturnum shows significant potential due to its high phytochemical content and extensive ethnobotanical applications. In contrast, C. diurnum, though equally promising, has been less explored. Here, we demonstrate that these neglected medicinal plants can be the next breakthrough in drug development. We also emphasize the significance of sustainable methods that assure the use and preservation of these rich resources.
Keywords: Cestrum diurnum; Cestrum nocturnum; Distribution; Diversity; Ethnobotany; Medicinal plant; Phytochemical